Patient and observer reported outcome measures to evaluate health-related quality of life in inherited metabolic diseases: a scoping review - Pascoal, Carlota (Orphanet J Rare Dis, 2018)
BACKGROUND: Health-related Quality of Life (HrQoL) is a multidimensional measure, which has gained clinical and social relevance. Implementation of a patient-centred approach to both clinical research and care settings, has increased the recognition of patient and/or observer reported outcome measures (PROMs or ObsROMs) as informative and reliable tools for HrQoL assessment. Inherited Metabolic Diseases (IMDs) are a group of heterogeneous conditions with phenotypes ranging from mild to severe and mostly lacking effective therapies. Consequently, HrQoL evaluation is particularly relevant. OBJECTIVES: We aimed to: (1) identify patient and/or caregiver-reported HrQoL instruments used among IMDs; (2) identify the main results of the application of each HrQoL tool and (3) evaluate the main limitations of HrQoL instruments and study design/methodology in IMDs. METHODS: A scoping review was conducted using methods outlined by Arksey and O’Malley. Additionally, we critically analysed each article to identify the HrQoL study drawbacks. RESULTS: Of the 1954 studies identified, 131 addressed HrQoL of IMDs patients using PROMs and/or ObsROMs, both in observational or interventional studies. In total, we identified 32 HrQoL instruments destined to self- or proxy-completion; only 2% were disease-specific. Multiple tools (both generic and disease-specific) proved to be responsive to changes in HrQoL; the SF-36 and PedsQL questionnaires were the most frequently used in the adult and pediatric populations, respectively. Furthermore, proxy data often demonstrated to be a reliable approach complementing self-reported HrQoL scores. Nevertheless, numerous limitations were identified especially due to the rarity of these conditions. CONCLUSIONS: HrQoL is still not frequently assessed in IMDs. However, our results show successful examples of the use of patient-reported HrQoL instruments in this field. The importance of HrQoL measurement for clinical research and therapy development, incites to further research in HrQoL PROMs’ and ObsROMs’ creation and validation in IMDs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13023-018-0953-9) contains supplementary material, which is available to authorized users.